Bibliometric Analysis of International Scientific Production on the Management of Happiness and Well-Being in Organizations - Núñez-Sánchez, José Manuel; Jambrino-Maldonado, Carmen; Rando-Cueto, Dolores; Iglesias-Sánchez, Patricia Pilar; De-las-Heras-Pedrosa, Carlos (MDPI, 2022)
The interest of the scientific community and, consequently, the scientific production of topics on happiness and well-being at work, or the management of happiness in organizations, has been increasing over the years. The main objective of this bibliometric analysis is to determine the evolution of the concepts referred to in published scientific works. Bibliometric methods and techniques are used to analyze the themes and the most relevant trends, the number of papers and their citations, and the main institutions, and to highlight areas where the most research has been done on these issues. In addition to the review of the scientific literature, 312 studies are analyzed and net-mapped. The most outstanding results are the increase in the number of papers and citations during the health pandemic caused by COVID-19; the importance given to the transversality of wellbeing programs in corporations; and the greater frequency of research on the benefits of promoting the improvement of quality of life for work performance and its social impact.
Keywords: Felicidad; Bienestar social; Conducta en las organizaciones; Empresas-Gestión; Bibliometría; Calidad de vida en el trabajo; Happiness at work; Happiness management; Organizational well-being; Organizations; Business management